2019
DOI: 10.1016/j.puhe.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dietary patterns and stunting in preschool children: a cohort analysis from Kwale, Kenya

Abstract: Objectives: Stunting is a significant cause of poor cognitive performance and lower school achievement. Stunting is observed among preschool children in several areas in Africa; however, not all children are affected, and children with and without stunting are seen in the same communities. Therefore, this study aimed to identify nutritional and other factors that prevent stunting that may exist in local communities. Study design: This is a prospective cohort study. Methods: Data were extracted from the Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
5
14
0
2
Order By: Relevance
“…Comparing dietary patterns among different populations is a difficult task due to their cultural, geographical, and social characteristics. Yet, our results are consistent with those reported by other studies 9,27 . In our study, children with eating habits mostly consistent with a "T" pattern (characterized by maize foods like tortillas and Mexican antojitos, as well as beans and eggs) were more likely to present stunting -an indicator of long-term malnutrition.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Comparing dietary patterns among different populations is a difficult task due to their cultural, geographical, and social characteristics. Yet, our results are consistent with those reported by other studies 9,27 . In our study, children with eating habits mostly consistent with a "T" pattern (characterized by maize foods like tortillas and Mexican antojitos, as well as beans and eggs) were more likely to present stunting -an indicator of long-term malnutrition.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, children with eating habits mostly consistent with a "T" pattern (characterized by maize foods like tortillas and Mexican antojitos, as well as beans and eggs) were more likely to present stunting -an indicator of long-term malnutrition. This finding is in line with those reported by a study conducted with preschool children from a rural area of Kenya, where the risk for stunting was higher among children who consumed the traditional pattern -mainly represented by maize foods, fruits, and low dietary diversity 27 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A large number of observational studies have shown that poor socioeconomic condition, unreasonable addition of supplementary food, household food insecurity, diseases of children (e.g. recurrent respiratory infections and diarrhea), inadequate maternal nutritional status, and low education level of caregivers are all associated with the malnutrition of children [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one in four children (26.2%) is estimated to be stunted in Kenya [ 10 ]. Tanaka et al reported that the traditional diet pattern had low dietary diversity in their research in Kenya, and children fed by the traditional diets had a higher risk of stunting compared with those who were fed by non-traditional diet patterns [ 11 ]. Since dietary diversity for children depends on caregivers’ knowledge, attitude, and practice [ 12 ], it is essential to provide caregivers enough information about the appropriate feeding of children, including dietary diversities by health staff members during antenatal and postnatal care.…”
Section: Introductionmentioning
confidence: 99%